Decision Making System for Race Car Modification Vleg Selection Using AHP and Moora Method - Alhabib, Muhammad Farhan; Hasugian, Abdul Halim (Sistemasi: Jurnal Sistem Informasi, 2024)
In the market, there are many different brands and types of modified vlegs, making vehicle owners often confused in making the optimal decision. Therefore, it is very important to have a decision-making system that can help vehicle owners in choosing the best modified wheels based on relevant criteria). In this study, researchers will develop a decision-making system that uses the Analytical Hierarchy Process (AHP) and Multi-Objective Optimization by Ratio Analysis (MOORA) methods to help vehicle owners in choosing the best modified wheels that best suit racing needs. In applying the AHP and MOORA algorithms to the SPK for selecting car tire wheels, 4 criteria are used, namely suitability, price, durability and design. Suggestions for further research can be used to add other relevant criteria in the selection of car tire wheels.